Perancangan Enterprise Architecture Menggunakan TOGAF ADM pada PT. Hafintech Prima Mandiri - Ahmad Haqqul Fikri; Welly Purnomo; Widhy Hayuhardhika Nugraha Putra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Hafintech Prima Mandiri is a company engaged in coding machine, which functions to print in all packaging media such as plastic bottles, cans, parallels and others. Services provided to corporate customers use manual systems and simple applications such as Microsoft Office, Microsoft Excel, WhatsApp, and Email, it can be said that understanding the role of the IS / IT field in a company is still lacking. Currently PT. Hafintech Prima Mandiri is demanded to further improve the quality of after sales service in terms of speed of service, clear information, and to satisfy customers. To overcome the above problems, PT. Hafintech Prima Mandiri should have a SI / IT that is fast, efficient, and connected in one network. To overcome the problems that exist at PT. Hafintech Prima Mandiri needs the design of enterprise enterprise architecture to align business strategy with IS / IT strategy, and careful planning is needed to plan and manage SI / IT. In this study, designing enterprise architecture using TOGAF (The Open Group Architecture Framework) with the ADM method (architecture develoment method). Limitations on the study include the Preliminary phase, Requirements Management phase, Phase A Architecture Vision, Phase B Business Architecture, Phase C Information System Architecture, and Phase D Technolghy Architecture. This enterprise architecture design will produce a proposed blueprint for business architecture, data architecture, application architecture, and technology architecture as a reference for PT. Hafintech Prima Mandiri.